PVC pipe and its preparation method and application
Patent Information
- Application Number
- CN202610807924.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-10-13
AI Technical Summary
[0007]为解决现有技术中存在的回收PVC树脂掺杂含量70%以上时应用无法兼具优良的维卡软化点,低温韧性和层间剥离强度的技术问题,本发明的首要目的是提供一种PVC管材
本发明通过在内层和外层使用偏苯三酸三辛酯和/或对苯二甲酸二辛酯作为增塑剂,并在中间层使用邻苯二甲酸二异壬酯和/或邻苯二甲酸二异癸酯作为辅助增塑剂,内层或外层中增塑剂的质量含量与中间层中辅助增塑剂的质量含量之比为1~2.5,加工过程中内层和外层增塑剂向中间层定向迁移并与辅助增塑剂协同形成互穿网络结构,显著提高了层间剥离强度,同时赋予管材优异的耐热性、低温抗冲击性能和阻燃性,且中间层中回收PVC含量70%以上,实现了回收PVC树脂的利用,适用于电工套管和回收管材领域。
Smart Images

Figure CN122896489A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of PVC pipe technology, and in particular relates to a PVC pipe, its preparation method and application. Background Technology
[0002] PVC electrical conduit has become the most widely used cable protection material in building electrical installations due to its excellent electrical insulation, flame retardancy, corrosion resistance, cost-effectiveness, and ease of processing. With the increasing stringency of building safety standards and energy conservation and environmental protection requirements, the market has placed higher demands on the performance of PVC electrical conduit: on the one hand, in certain special environments or under high line loads, the conduit is required to withstand temperatures of 93℃ and above for extended periods without softening or deformation; on the other hand, during construction or storage in cold regions, the conduit is required to maintain good toughness at low temperatures (such as -15℃) to prevent brittleness during installation.
[0003] Meanwhile, from the perspective of circular economy and sustainable development, how to make extensive use of recycled plastics to reduce the consumption of primary resources and waste pollution while ensuring product performance has become an urgent issue in the industry. As a major type of plastic, PVC generates a large amount of waste after its products are scrapped. High-value recycling and reuse of PVC has significant environmental and economic benefits.
[0004] However, using recycled PVC (especially post-consumer recycled PVC from complex sources) in the manufacture of high-performance electrical conduits faces a series of technical challenges. First, recycled PVC has undergone thermal history during previous use and processing, potentially leading to chain breakage and the depletion of its original heat stabilizer system. This results in a significantly lower heat distortion temperature (Vicat softening point) compared to virgin material, making it difficult to meet the high standard requirement of above 93°C. Second, plasticizers in recycled materials may migrate or volatilize, and the introduction of impurities (such as other plastics and fillers) disrupts the material's homogeneity, increasing its brittleness at low temperatures and deteriorating its impact resistance. Furthermore, the complex composition and unstable flowability of recycled PVC mean that simply using it as the intermediate layer in multi-layer pipes can easily lead to insufficient interlayer bonding due to differences in molecular polarity, melt viscosity, and shrinkage compared to virgin layers. During use, under heat or stress, delamination and peeling can easily occur between the pipe layers, severely affecting the overall structural strength and long-term reliability of the pipeline.
[0005] To address the aforementioned issues, existing technologies have attempted to use virgin materials as inner and outer layers and recycled materials as the middle layer. However, these technologies typically suffer from low recycled material content (generally below 30%), or sacrifice overall product performance (e.g., reducing heat resistance) to accommodate the performance of recycled materials. Some studies have also attempted to improve the performance of recycled materials through simple blending modification, but these have failed to systematically solve the problems of interfacial bonding and performance synergy in multilayer structures.
[0006] Therefore, developing a PVC pipe with a recycled PVC resin doping content of over 70% that can combine excellent Vicat softening point, low-temperature toughness, and interlayer peel strength is of significant research importance and application value. Summary of the Invention
[0007] To address the technical problem in existing technologies where recycled PVC resin with a doping content of over 70% cannot simultaneously achieve excellent Vicat softening point, low-temperature toughness, and interlayer peel strength, the primary objective of this invention is to provide a PVC pipe.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned PVC pipe.
[0009] Another object of the present invention is to provide the application of the above-mentioned PVC pipes in electrical conduits and recycled pipes.
[0010] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: This invention protects a PVC pipe material comprising a three-layer composite structure, an inner layer, a middle layer, and an outer layer; The inner or outer layer comprises the following components in parts by weight: 100 parts of first PVC resin, 3-6 parts of calcium-zinc heat stabilizer, 10-25 parts of plasticizer, 5-12 parts of impact modifier, 3-8 parts of heat-resistant modifier, 1-3 parts of processing aid, and 1-3 parts of lubricant. The plasticizer includes trioctyl trimellitate and / or dioctyl terephthalate; The degree of polymerization of the first PVC resin is 1300 or higher; The intermediate layer comprises the following components in parts by weight: 100 parts recycled PVC resin, 10-20 parts toughening agent, 2-4 parts calcium-zinc heat stabilizer, and 8-15 parts auxiliary plasticizer. The auxiliary plasticizer is diisononyl phthalate and / or diisodecyl phthalate; The ratio of the mass content of plasticizer in the inner or outer layer to the mass content of auxiliary plasticizer in the intermediate layer is 1 to 2.5.
[0011] In the formulation design of the inner and outer layers, the plasticizers selected in this invention are trioctyl trimellitate (TOTM) and / or dioctyl terephthalate (DOTP). Their molecular structure contains both benzene rings and ester bonds, exhibiting excellent compatibility with PVC resin. Furthermore, their relatively large molecular weight and low migration properties significantly improve the plasticizing efficiency of PVC materials and the heat distortion temperature of the finished product. In addition, combined with other components in the inner and outer layers, the inner and outer layers serve as heat-resistant toughening layers with both high heat resistance and good low-temperature toughness, providing high-performance protection for the entire casing.
[0012] In the formulation of the intermediate layer, the present invention uses recycled PVC resin as the matrix and selects auxiliary plasticizers, such as diisononyl phthalate (DINP) or diisodecyl phthalate (DIDP). The auxiliary plasticizers themselves can improve the processing fluidity of recycled PVC resin and can synergistically interact with plasticizers migrating from the inner and outer layers to form an interpenetrating network.
[0013] The interface region between the inner and outer layers and the intermediate layer exhibits extremely high toughness and adhesion due to the enrichment of plasticizers, significantly enhancing the interlayer peel strength between the inner and outer layers and the intermediate layer. TOTM or DOTP plasticizer molecules have long chain structures, enabling them to physically entangle with PVC molecular chains and lock the PVC layers on both sides. This method, which involves the in-situ migration of active components during processing and the spontaneous formation of a reinforced interface, produces a stronger and more stable interlayer bonding force compared to traditional methods of simple physical bonding or the addition of compatibilizers.
[0014] This invention limits the degree of polymerization of the first PVC resin in both the inner and outer layers to 1300 or higher, and the molecular chain entanglement density to a critical threshold or higher, forming a stable physical cross-linked network. This network physically hinders the migration of plasticizer molecules, controlling their migration rate within an appropriate range, thereby rationally controlling the concentration of plasticizer at the interface between the inner and outer layers and the intermediate layer. When the degree of polymerization of the first PVC resin is lower than 1300, the molecular chain length is insufficient to form a sufficiently entangled physical network, and the diffusion coefficient of the plasticizer in the PVC matrix increases significantly, leading to two adverse consequences: First, excessive migration of the plasticizer during processing and use causes loss of plasticizer from both the inner and outer layers, reducing heat resistance, and disrupting the concentration gradient structure at the interface, weakening the tight bonding effect with the intermediate layer; Second, excessively migrated plasticizer may migrate to the surface of the sleeve, causing surface stickiness and affecting performance.
[0015] Preferably, the degree of polymerization of the first PVC resin is 1300~1700.
[0016] Preferably, the plasticizers in the inner and outer layers further include epoxidized soybean oil. Preferably, the epoxidized soybean oil accounts for less than 50% of the plasticizer by weight. More preferably, the epoxidized soybean oil accounts for less than 40% of the plasticizer by weight.
[0017] The epoxy groups in epoxidized soybean oil ESO can undergo ring-opening addition reactions with polar groups that may be present in the intermediate layer formulation (such as vinyl acetate in EVA and maleic anhydride in CPE-g-MAH), forming a chemically bonded interface and further enhancing the interlayer bonding strength. However, the weight ratio of ESO in the plasticizer must be controlled to not exceed 40%, otherwise the increased overall migration will affect the formation of the interfacial gradient structure and may lead to a decrease in the heat resistance of the inner and outer layers.
[0018] Preferably, the inner layer thickness accounts for 30-40% of the thickness of the PVC pipe.
[0019] Preferably, the outer layer thickness accounts for 30-40% of the thickness of the PVC pipe.
[0020] Preferably, the thickness of the intermediate layer accounts for 20-40% of the thickness of the PVC pipe.
[0021] The recycled PVC resin mentioned in this invention has a doping content of 70% or more, which refers to the percentage of recycled PVC resin in the intermediate layer by mass.
[0022] Preferably, the recycled PVC resin contains ≥85% PVC resin by mass.
[0023] The recycled PVC resin comes from waste wire sheaths, profiles, etc.
[0024] Preferably, the recycled PVC resin has a PVC resin content of ≥92% by mass, an ash content of ≤5%, and a moisture content of ≤1.0%.
[0025] Preferably, the average particle size of the recycled PVC resin is 80-120 mesh.
[0026] More preferably, the average particle size of the recycled PVC resin is 100 mesh.
[0027] Preferably, the impact modifier is at least one of chlorinated polyethylene or acrylate impact modifiers.
[0028] Preferably, the processing aid is an acrylate polymer.
[0029] Preferably, the heat-resistant modifier is an α-methylstyrene oligomer.
[0030] Preferably, the toughening agent of the intermediate layer is at least one of ethylene-vinyl acetate copolymer or maleic anhydride-grafted chlorinated polyethylene.
[0031] Preferably, the vinyl acetate content of the ethylene-vinyl acetate copolymer is 40-45%.
[0032] Preferably, the toughening agent of the intermediate layer is ethylene-vinyl acetate copolymer and maleic anhydride-grafted chlorinated polyethylene in a weight ratio of 3~7:3~7.
[0033] This invention also protects the method for preparing the above-mentioned PVC pipe, comprising the following steps: S1. Weigh the components of the inner layer, middle layer and outer layer according to the formula, and mix them sequentially at high speed; S2. Co-extrude the materials obtained in step S1 separately; S3. Three layers are co-extruded at a die temperature of 175~190℃ to form a three-layer composite tube blank; S4. Shaping and cooling, followed by traction cutting to obtain the PVC pipe.
[0034] Preferably, in step S1, the final mixing temperature of the inner and outer layers is controlled at 115~125℃, and the final mixing temperature of the middle layer is controlled at 105~115℃.
[0035] Preferably, the co-extrusion equipment is a twin-screw extruder.
[0036] Preferably, in step S2, the extrusion temperature of the inner and outer layers is set to 150~160℃ in zone 1, 160~170℃ in zone 2, 165~175℃ in zone 3, 170~180℃ in zone 4, and 175~185℃ at the die head.
[0037] The application of the aforementioned PVC pipes in electrical conduits and recycled pipes is also within the scope of protection of this invention.
[0038] Compared with the prior art, the present invention has the following beneficial effects: This invention uses trioctyl trimellitate and / or dioctyl terephthalate as plasticizers in the inner and outer layers, and diisononyl phthalate and / or diisodecyl phthalate as auxiliary plasticizers in the intermediate layer. The mass ratio of the plasticizer in the inner or outer layer to the auxiliary plasticizer in the intermediate layer is 1 to 2.5. During processing, the plasticizers in the inner and outer layers migrate directionally to the intermediate layer and synergistically form an interpenetrating network structure with the auxiliary plasticizers, which significantly improves the interlayer peel strength. At the same time, it endows the pipe with excellent heat resistance, low-temperature impact resistance and flame retardancy. Moreover, the recycled PVC content in the intermediate layer is more than 70%, realizing the utilization of recycled PVC resin. It is suitable for the fields of electrical conduit and recycled pipe. Attached Figure Description
[0039] Figure 1 This is a schematic diagram of a PVC pipe structure. Detailed Implementation
[0040] The present invention is further illustrated below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions in the art or as recommended by the manufacturer; the raw materials and reagents used, unless otherwise specified, are all commercially available from the conventional market. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention are within the scope of protection claimed by the present invention.
[0041] I. Reagent Instructions First PVC resin #1: Xinjiang Tianye Co., Ltd., SG-5 type, degree of polymerization 1500; First PVC resin #2: Shaanxi Beiyuan Chemical Group Co., Ltd., SG-6 type, degree of polymerization 1300; First PVC resin #3: Tianjin Dagu Chemical Co., Ltd., SG-4 type, degree of polymerization 1700; First PVC resin #4: Xinjiang Zhongtai, P-450, degree of polymerization 1200.
[0042] Calcium-zinc heat stabilizer: Guangdong Weilinna New Materials Co., Ltd., calcium-zinc ratio 1:1.2, initial melting point ≥80℃; Recycled PVC resin #1: Powder with an average particle size of 100 mesh, self-developed and recycled, derived from waste wire sheaths and profiles, PVC content ≥92%, ash content ≤3%; Recycled PVC Resin #2: PVC recycled material, LJ, Suzhou Langjian Plastics Technology Co., Ltd., granules, PVC content ≥90%, ash content ≤3%; Toughening agent: Ethylene-vinyl acetate copolymer, 2803 (VA content 40%), DuPont, USA, VA content 40~45%, melt index 25~35 g / 10min; Toughening agent: Maleic anhydride grafted chlorinated polyethylene, CPE-135A grafted type, Weifang Zhongxu, grafting rate 0.8~1.2%, chlorine content 35~36%.
[0043] II. Experimental Methods Example 1 A high heat-resistant, impact-resistant, and environmentally friendly multilayer PVC pipe with a diameter of Φ16mm was prepared. It has a three-layer structure with a total wall thickness of approximately 1.5mm and a thickness ratio of inner layer: middle layer: outer layer = 35%:30%:35%. The ratio of the mass content of plasticizer in the inner or outer layer to the mass content of auxiliary plasticizer in the middle layer is 1.54. Components: Inner layer (reactive plasticizer content is 20 / 140.8 = 14.2%): First PVC resin #1, degree of polymerization 1500: 100kg; Calcium-zinc heat stabilizer: 4.5 kg; Reactive plasticizer: Trioctyl trimellitate (TOTM): 20 kg; Impact modifier CPE (135A): 8 kg; Heat-resistant modifier AMS oligomer: 5kg; ACR processing aid (ZBST-1): 2kg; Lubricant: Calcium stearate: 0.8 kg, Oxidized polyethylene wax: 0.5 kg; Intermediate layer (mass content of auxiliary plasticizer is 12 / 130=9.2%): 100 kg of recycled PVC powder (100 mesh, derived from waste wire sheathing and profiles); Toughening agent ethylene-vinyl acetate copolymer EVA (VA content 42%): 8 kg; Toughening agent maleic anhydride grafted chlorinated polyethylene CPE-g-MAH: 7kg; DINP (Dual Plasticizer) 12kg; Calcium and zinc stabilizer: 3 kg.
[0044] Outer layer: First PVC resin #1, degree of polymerization 1500: 100kg; Calcium-zinc heat stabilizer: 4.5 kg; Reactive plasticizer: Trioctyl trimellitate (TOTM): 20 kg; Impact modifier CPE (135A): 8 kg; Heat-resistant modifier AMS oligomer: 5kg; ACR processing aid (ZBST-1): 2kg; Lubricant: Calcium stearate: 0.8 kg, Oxidized polyethylene wax: 0.5 kg; Preparation method: S1. First, add the recycled PVC powder (intermediate layer), toughening agent ethylene-vinyl acetate copolymer (EVA), toughening agent maleic anhydride grafted chlorinated polyethylene (CPE-g-MAH), and 6 kg of diisononyl phthalate (DINP) to a low-speed mixer and premix for 5 minutes. Then, let it stand for 3 hours for pre-impregnation. Next, mix all materials separately according to the formula in a high-speed hot mixer. The final temperature of the inner and outer layer mixtures is 120°C, and the final temperature of the intermediate layer mixture is 110°C. Cool to 40°C and discharge. S2. Two 55-type conical twin-screw extruders are used. The virgin material extruder (for inner and outer layer mixing) has temperatures of 155 / 165 / 170 / 175 / 180℃; the recycled material extruder (for intermediate layer mixing) has temperatures of 150 / 160 / 165 / 170 / 175℃. The melt is pumped into a three-layer co-extrusion screw die at a temperature of 180℃. The screw speed is adjusted to ensure that the viscosities of the virgin and recycled melts are similar at the point of convergence.
[0045] S3. The tube blank is vacuum-shaped (-0.07MPa), spray-cooled (15℃ water), tracked, and cut to a fixed length to obtain the finished product.
[0046] Example 2 The experimental methods and components are the same as in Example 1, except that the plasticizer in the inner and outer layers is replaced with 20 kg of dioctyl terephthalate, while the content remains the same.
[0047] Example 3 The experimental methods and components are the same as in Example 1, except that the plasticizers in the inner or outer layer are replaced with trioctyl trimellitate and dioctyl terephthalate in a weight ratio of 1:1. That is, the plasticizers in the inner or outer layer are 10 kg of trioctyl trimellitate and 10 kg of dioctyl terephthalate, and the total plasticizer content in the inner or outer layer remains unchanged.
[0048] Example 4 The experimental methods and components are the same as in Example 1, except that there is 16 kg of plasticizer and 15 kg of auxiliary plasticizer. The ratio of the mass content of plasticizer (11.7%) in the inner or outer layer to the mass content of auxiliary plasticizer (11.3%) in the middle layer is 1.04.
[0049] Example 5 The experimental methods and components are the same as in Example 1, except that there is 20 kg of plasticizer and 10 kg of auxiliary plasticizer. The ratio of the mass content of plasticizer (14.2%) in the inner or outer layer to the mass content of auxiliary plasticizer (7.8%) in the middle layer is 1.82.
[0050] Example 6 The experimental methods and components are the same as in Example 1, except that the recycled PVC resin in the intermediate layer is recycled PVC resin 2#.
[0051] Example 7 The experimental methods and components were the same as in Example 1, except that the first PVC resin in the inner and outer layers was first PVC resin 2# with a degree of polymerization of 1300.
[0052] Example 8 The experimental methods and components were the same as in Example 1, except that the first PVC resin in the inner and outer layers was first PVC resin 3# with a degree of polymerization of 1700.
[0053] Example 9 The experimental methods and components were the same as in Example 1, except that the plasticizer for the inner and outer layers was 20 parts of TOTM and 8 kg of epoxidized soybean oil, with the weight ratio of epoxidized soybean oil to plasticizer being 40%.
[0054] Example 10 The experimental methods and components are the same as in Example 1, except that the plasticizer for the inner and outer layers is 20 parts of TOTM and 10 kg of epoxidized soybean oil, with the weight ratio of epoxidized soybean oil to plasticizer being 50%.
[0055] Example 11 The experimental methods and components were the same as in Example 1, except that the thickness ratio of the PVC pipe was inner layer: middle layer: outer layer = 30%: 40%: 30%.
[0056] Example 12 The experimental methods and components were the same as in Example 1, except that the thickness ratio of the PVC pipe was inner layer: middle layer: outer layer = 40%: 20%: 40%.
[0057] Examples 13-14 The experimental method is the same as in Example 1, and the components are shown in Table 1, wherein: Example 13: 10 kg of plasticizer and 9 kg of auxiliary plasticizer, wherein the mass content of plasticizer in the inner or outer layer (7.7%) is 0.69 to the mass content of auxiliary plasticizer in the intermediate layer (11.1%). Example 14: 25 kg of plasticizer and 8.8 kg of auxiliary plasticizer, wherein the mass content of plasticizer in the inner or outer layer (17.2%) is 2.49 to the mass content of auxiliary plasticizer in the intermediate layer (6.9%). Table 1 Components of Examples 13 and 14
[0058] Comparative Example 1 The experimental methods and components are the same as in Example 1, except that there is 25 kg of plasticizer and 8.5 kg of auxiliary plasticizer, and the ratio of the mass content of plasticizer in the inner or outer layer to the mass content of auxiliary plasticizer in the intermediate layer is 2.55.
[0059] Comparative Example 2 The experimental methods and components are the same as in Example 1, except that 10 kg of plasticizer and 15 kg of auxiliary plasticizer are used, and the mass content of plasticizer in the inner or outer layer is 0.68 to the mass content of auxiliary plasticizer in the middle layer.
[0060] Comparative Example 3 The experimental methods and components were the same as in Example 1, except that an equal amount of di(2-propylheptyl) phthalate (DPHP), a low-migration non-reactive plasticizer, was used as an alternative to plasticizer TOTM.
[0061] Comparative Example 4 The experimental methods and components are the same as in Example 1, except that the first PVC resin in the inner and outer layers is first PVC resin 4# with a degree of polymerization of 1200.
[0062] III. Test Indicators (1) Vicat softening point (VST / B50): Tested according to GB / T 8802; (2) Low temperature impact test (-15℃ / 1kg / 1m): 10 specimens, tested according to GB / T 14823.2; (3) Interlayer peel strength (N / cm): Self-made fixture, 90° peel test; (4) Oxygen Index (OI): According to GB / T 2406.2, the oxygen index (OI) is the core indicator for measuring the flame retardancy of materials. It is defined as the minimum percentage of oxygen by volume required for a unit volume of material to sustain combustion in an oxygen-nitrogen mixture. OI ≥ 32%: Meets the flame-retardant PVC material standard specified in GB / T 8815-2008; OI 28%~32%: Prolonged self-extinguishing time after flame removal and decreased flame retardancy; OI < 28%: Flammable in air, not suitable for electrical conduits; (5) Content of recycled PVC resin: the percentage of recycled PVC resin in the intermediate layer by mass.
[0063] IV. Experimental Results Table 2. Test Results of Examples / Comparative Examples
[0064] In Comparative Example 1, the ratio of the mass content of the plasticizer to the mass content of the auxiliary plasticizer in the intermediate layer was 2.55, which exceeded the range of 1 to 2.5 defined in this application. Compared with Example 1, the Vicat softening point dropped significantly to 89°C, the interlayer peel strength dropped significantly to 2.8 N / cm, the relative content of plasticizers in the inner and outer layers increased, the migration rate was too fast, exceeding the synergistic ability of the intermediate layer auxiliary plasticizer DINP, destroying the interpenetrating network, and the excessive plasticizer formed an over-swelling zone at the interface, destroying the physical entanglement network of PVC molecular chains and reducing the interlayer bonding strength; the plasticizers in the inner and outer layers were severely lost, and the heat resistance decreased; at the same time, the intermediate layer was over-plasticized, and the low-temperature toughness deteriorated.
[0065] In Comparative Example 2, the ratio of the mass content of the plasticizer to the mass content of the auxiliary plasticizer in the intermediate layer was 0.68. The plasticizer concentration in both the inner and outer layers was insufficient, resulting in weak migration driving force and an inability to form a sufficient plasticizer gradient and interpenetrating network structure at the interface. The auxiliary plasticizer in the intermediate layer was relatively excessive, which diluted the migrated TOTM and weakened the synergistic effect. The interfacial bonding was insufficient, leading to a decrease in peel strength. The plasticization of both the inner and outer layers was insufficient, resulting in a simultaneous decrease in heat resistance and low-temperature toughness.
[0066] Comparative Example 3 replaced the inner and outer layer plasticizer TOTM with DPHP (di(2-propylheptyl) phthalate), a low-migration, non-reactive plasticizer. DPHP's molecular structure lacks long-chain entanglement ability, making it unable to form an effective interpenetrating network with the intermediate DINP layer; its migration is too low, making it difficult to migrate to the interface even at processing temperatures, thus failing to form a concentration gradient or interfacial plasticizing layer, resulting in reduced peel strength; the inner and outer layers have low plasticizing efficiency and poor heat resistance; DPHP itself contributes less to the flame retardancy of PVC than TOTM.
[0067] Comparative Example 4 uses the first PVC resin with a degree of polymerization of 1200. The physical entanglement density is insufficient and cannot effectively prevent the migration of TOTM. The plasticizer migrates excessively during processing and use. On the one hand, the plasticizer in the inner and outer layers is lost, and the heat resistance decreases. On the other hand, the concentration of plasticizer in the middle layer is too high, which destroys the interface structure. The plasticizer is unevenly distributed at the interface, the interpenetrating network is incomplete, and the peel strength decreases significantly. At low temperature, the molecular chain is short and the free volume is large, which increases brittleness and deteriorates the impact resistance.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A PVC pipe, characterized in that, It includes a three-layer composite structure: an inner layer, a middle layer, and an outer layer; The inner or outer layer comprises the following components in parts by weight: 100 parts of first PVC resin, 3-6 parts of calcium-zinc heat stabilizer, 10-25 parts of plasticizer, 5-12 parts of impact modifier, 3-8 parts of heat-resistant modifier, 1-3 parts of processing aid, and 1-3 parts of lubricant. The plasticizer includes trioctyl trimellitate and / or dioctyl terephthalate; The degree of polymerization of the first PVC resin is 1300 or higher; The intermediate layer comprises the following components in parts by weight: 100 parts recycled PVC resin, 10-20 parts toughening agent, 2-4 parts calcium-zinc heat stabilizer, and 8-15 parts auxiliary plasticizer. The auxiliary plasticizer is diisononyl phthalate and / or diisodecyl phthalate; The ratio of the mass content of plasticizer in the inner or outer layer to the mass content of auxiliary plasticizer in the intermediate layer is 1 to 2.
5.
2. The PVC pipe according to claim 1, characterized in that, The plasticizers in the inner and outer layers also include epoxidized soybean oil.
3. The PVC pipe according to claim 2, characterized in that, The epoxidized soybean oil accounts for less than 40% of the plasticizer by weight.
4. The PVC pipe according to claim 1, characterized in that, The recycled PVC resin contains ≥85% PVC resin by mass.
5. The PVC pipe according to claim 1, characterized in that, The inner layer thickness accounts for 30-40% of the PVC pipe thickness.
6. The PVC pipe according to claim 1, characterized in that, The outer layer thickness accounts for 30-40% of the thickness of the PVC pipe.
7. The PVC pipe according to claim 1, characterized in that, The thickness of the intermediate layer accounts for 20-40% of the thickness of the PVC pipe.
8. The PVC pipe according to claim 1, characterized in that, The degree of polymerization of the first PVC resin is 1300~1700.
9. A method for preparing the PVC pipe according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1. Weigh the components of the inner layer, middle layer and outer layer according to the formula, and mix them sequentially at high speed; S2. Co-extrude the materials obtained in step S1 separately; S3. Three layers are co-extruded at a die temperature of 175~190℃ to form a three-layer composite tube blank; S4. Shaping and cooling, followed by traction cutting to obtain the PVC pipe.
10. The application of the PVC pipe according to any one of claims 1 to 8 in electrical conduit and recycled pipe.